Dynamic RCST grouping for achieving high link capacities in mobile DVB-RCS networks - Chou, C. L.; Wang, S. Y. (My University, 2007)
A DVB-RCS system provides bidirectional connections between service providers and end users. Service providers deliver broadcast data through the forward link to end users while end users send back their data through the return link. The return link is composed of multiple access channels, which can be accessed by the MF-TDMA scheme. Over each channel, a time-slot includes a guard time duration for accommodating propagation delay uncertainties among RCSTs accessing the same channel. In a system with mobile RCSTs, the guard time duration may take a considerable portion of a time-slot for avoiding data collision. Guard time represents bandwidth overhead of the system and large guard time causes significant link capacity reduction. In this paper, we first investigate the problem of link capacity reduction when the DVB-RCS standard, which is originally designed for fixed RCSTs, is directly used with mobile RCSTs without modification. Then, we propose a dynamic RCST grouping mechanism for DVB-RCS to achieve high link capacity with mobile RCSTs.